2017
DOI: 10.1159/000462977
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Treatment with Prolonged Exposure for Co-Occurring Full or Subthreshold Posttraumatic Stress Disorder and Substance Use Disorders: A Randomized Clinical Trial

Abstract: Background: To test whether an integrated prolonged exposure (PE) approach could address posttraumatic stress disorder (PTSD) symptoms effectively in individuals with co-occurring substance use disorders (SUD), we compared concurrent treatment of PTSD and SUD using PE (COPE) to relapse prevention therapy (RPT) for SUD and an active monitoring control group (AMCG). Methods: We conducted a randomized 12-week trial with participants (n = 110; 64% males; 59% African Americans) who met Diagnostic and Statistical Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 51 publications
8
83
1
1
Order By: Relevance
“…Furthermore, the current study provides indications for treatment matching by degree of emotion regulation difficulties. Without taking baseline level of ED into consideration, Ruglass et al (2017) showed that those who received either COPE or RPT demonstrated statistically significant improvements in both PTSD and SUD outcomes when compared to the control group. The present study’s examination of baseline level of ED as a moderator revealed indications for differential treatment selection.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Furthermore, the current study provides indications for treatment matching by degree of emotion regulation difficulties. Without taking baseline level of ED into consideration, Ruglass et al (2017) showed that those who received either COPE or RPT demonstrated statistically significant improvements in both PTSD and SUD outcomes when compared to the control group. The present study’s examination of baseline level of ED as a moderator revealed indications for differential treatment selection.…”
Section: Discussionmentioning
confidence: 96%
“…The institutional review board of the City College of New York approved all procedures. Detailed descriptions of all study procedures including randomization, the interventions and fidelity, and data collection are described in Ruglass et al (2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this research gap, our study compares Seeking Safety plus treatment as usual (TAU) to Relapse Prevention Training (RPT) plus TAU and to a TAU control. RPT, a standard SUD treatment, was chosen as an active control condition because it has been shown to be effective for reducing symptoms of PTSD and substance use in individuals with co-occurring PTSD and SUD (Hien, Cohen, Miele, Litt, & Capstick, 2004;Ruglass et al, 2017). The primary hypothesis was that Seeking Safety plus TAU would outperform TAU alone on PTSD reduction, but not differ from RPT plus TAU.…”
Section: Introductionmentioning
confidence: 99%